Epidermolysis bullosa in Greece: the patients’ journey so far - Verroiou, Ioanna; Tzanetakou, Vassiliki N.; Katsarou, Alexandra; Zambruno, Giovanna; Castiglia, Daniele; Rigopoulos, Dimitrios; Stratigos, Alexander J. (International Journal of Research in Dermatology, 2018)
Background: Hereditary epidermolysis bullosa (EB) represents a group of rare, inherited disorders with different penetrance patterns characterized by skin fragility and easy inducibility of blisters. Mucosal involvement of internal organs may occur. As no published data on EB in Greece exist, this study aimed to record demographics and clinical characteristics of EB patients. Another objective was to identify the associations among clinical characteristics of different types in connection with immunofluorescence mapping (IMF) findings and molecular analysis (MA) used for the laboratory diagnosis of the disease. Methods: This is a descriptive study conducted at the outpatient clinic of rare diseases of Andreas Sygros Hospital, Athens, Greece from March 2012 until February 2015. Adults and children presenting with EB were enrolled. Patients underwent a thorough clinical and laboratory assessment. Specific laboratory analyses were performed in Rome and two sets of data based on IFM and MA were collected. Results: In total, 41 patients were enrolled. Prevalence rate of EB was 0.024%. The most frequent type was dystrophic EB, as it affected 20 patients (48.8%). Twelve patients (29.3%) were diagnosed with EB simplex, 6 patients (14.6%) with Kindler syndrome and 3 (7.3%) with junctional EB. IFM was performed in 26 patients and MA in 8 patients. The concordance among clinical and laboratory diagnosis was 88.5%. Conclusions: This study is the first report on hereditary EB in Greece. Since there is a lack in diagnostic management of EB, we would strongly encourage an effort to perform the required laboratory tests in Greece.